Development of a Conceptual Model for Intelligent Software System Designing - Mahmudova, Shafagat (Review of Information Engineering and Applications, 2022)
This article provides information on the design of intelligent software systems. An intelligent software system refers to any software using artificial intelligence to analyze and interpret data or to communicate with systems and people. The article substantiates the relevance of the issue and highlights existing problems. The following factors are taken into consideration when assessing the problems of intelligent software system designing: easy data collection, low cost of developing intelligent systems, availability of experts and necessary resources (computers, program developers, software, etc.). The article also reports of related studies and identifies application areas. A conceptual model is developed for the design of intelligent software systems. The stages, components, directions, etc. indicated in the conceptual model for the design of intelligent software systems are studied and the characteristics of each are determined. Some examples of design types by the fields of activity are identified. The developed model can be used in the design of intelligent software systems related to any instrumental programming.